0
$\begingroup$

In the Ashok Das book "Lectures on quantum field theory" , it's written that in page 76 : therefore, the matrix $ S~ \gamma^0~ S^\dagger ~ \gamma^0$ must be proportional to the identity matrix (this can be easily checked by taking a linear combination of the sixteen basis matrices in (2.100) and calculating the commutator with $\gamma^\mu$ ). As a result, we can denote

$$ S~ \gamma^0~ S^\dagger ~ \gamma^0 = b~ 1 $$

Do any one know how this can be made?

Edit

Where Dirac equation

$$iγ^ μ ∂ μ − m ψ(x) = 0 .$$

Under a Lorentz transformation $$x^ μ → x ^{′ μ} = Λ^μ_ν x^ ν ,$$

the transformed equation has the form

$$iγ^ μ ∂_μ′ − m ψ ′ (x ′ ) = 0,$$

where

$$\psi'(x') = \psi'(\Lambda x)= S(\Lambda) \psi(x) $$

and

$$\psi(x) = S^{-1}(\Lambda) \psi'(x') .$$

$\endgroup$
  • $\begingroup$ where the Dirac spinor $\psi' = S \psi $, please look Equ. (3.42) in the book .. $\endgroup$ – S.S. Dec 12 '16 at 17:32
  • $\begingroup$ I thought it's a famous book like Peskin, so it's here on this link : dropbox.com/s/v3h25xfaee14nab/… $\endgroup$ – S.S. Dec 12 '16 at 17:48
  • $\begingroup$ The covariance of Dirac equation is a whole section , so it's better to seen in the book, also Equ. (2.100) and (3.42) consist of many equations .. any way i think studying Dirac equation is common in different references, the transformation matrices and so .. $\endgroup$ – S.S. Dec 12 '16 at 17:52
  • $\begingroup$ No problem , i will add my question .. $\endgroup$ – S.S. Dec 12 '16 at 17:53
1
$\begingroup$

We need two lemmas:

$$B\mathrm e^A B^{-1}=\mathrm e^{BAB^{-1}}\tag{1}$$ (see here for the proof).

And the fact that the gamma matrices satisfy $$(\gamma^{\mu})^\dagger=\gamma^0\gamma^\mu\gamma^0\tag{2}$$ (the proof is easy; one just considers the cases $\mu=0$ and $\mu=i$ separately).


Here, $S$ is defined as $$ S=\exp\left[-\frac i2 \omega_{\mu\nu}\gamma^{[\mu}\gamma^{\nu]}\right] $$ where $\gamma^\mu$ are the Dirac gamma matrices.

Using $(1)$ together with $(\gamma^0)^2=1$, we can see that $$ \gamma^0 S\gamma^0\overset{(1)}=\exp\left[-\frac i2 \omega_{\mu\nu}\gamma^0\gamma^{[\mu}\gamma^{\nu]}\gamma^0\right] \tag{A} $$

Now, we use $(2)$ together with $(\gamma^0)^2=1$ to conclude that $$ \gamma^0\gamma^{[\mu}\gamma^{\nu]}\gamma^0=\gamma^0\gamma^{[\mu}\gamma^0\gamma^0\gamma^{\nu]}\gamma^0\overset{(2)}=-(\gamma^{[\mu}\gamma^{\nu]})^\dagger\tag{B} $$

Finally, using $(\mathrm A)$ and $(\mathrm B)$, we see that $$ \gamma^0 S\gamma^0=\exp\left[+\frac i2 \omega_{\mu\nu}(\gamma^{[\mu}\gamma^{\nu]})^\dagger\right]=S^\dagger $$ as we wanted to prove.

$\endgroup$
  • $\begingroup$ Thanks. You mean here with the brackets $\gamma^{[\mu} \gamma^{\nu]}$ that they are anti commuting matrices ? $\endgroup$ – S.S. Dec 12 '16 at 20:21
  • $\begingroup$ Yes. More precisely, $\gamma^{[\mu}\gamma^{\nu]}\equiv\frac12 [\gamma^\mu,\gamma^\nu]$. $\endgroup$ – AccidentalFourierTransform Dec 12 '16 at 22:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.